A Study of The Perceptions on Customer Behavioral Intention Of Buy Online Pick Up In Store Services In Convenience Store Industry (Journal of Business and Management, 2022)
The Omnichannel adoption strategy in Indonesia is still low. After the Covid-19 pandemic, many companies are implementing Buy Online Pick Up in Stores. The purpose of this study is to assess the relationship customer acceptance perception factors on Buy Online Pick Up In Store of KlikIndomaret and Alfagift towards Behavioral Intention. The author used the UTAUT2 Theory. In this study the author uses a mix method approach. In-depth interviews and netnography and analyse it using manual coding and the quantitative approach using questionnaires.The descriptive analysis using Multiple Linear Regression (MLR), Cross Tabulation and Chi-square. The result of this study is the significant positive effect of the customer perception on the intention to use Buy Online Pick Up In Store service was only for Performance Expectancy, Compatibility,Trust, Service Effectiveness and Problem Handling. Other factors have a negative effect of intention to use Buy Online Pick Up In Store service. The demographic also plays important roles especially Age, gender and experience has a positive effect on Trust. In this study, the strategy was obtained which can be used as a benchmark for companies.Keywords : Customer Perception; Behavioral Intention; Buy Online Pick Up In Store; UTAUT2 Theory; Mixed method; Multiple Linear Regression (MLR)